The incentive effects of project governance elements on agents in agent-led construction of social security housing projects - Chen, Zhiqi; Yao, Liming; Zheng, Minghui; Zhang, Ling (International Journal of Strategic Property Management, 2024)
The agent-led construction system is a construction mode that emphasizes the introduction of professional management teams instead of government departments to develop public projects in China, including social security housing. In reality, the problem in practice is that the government owners’ management system of the agent market is not sound enough, and it cannot effectively motivate the agents. Existing research has not paid enough attention to this agent construction market. To reveal the effective incentives of agent developers, using the stimulus–organism–response theory, this study constructed a structural equation model and proposed a research hypothesis about the effect of project governance elements on project performance. The study found that governance elements including internal contractual governance, external contractual governance, and relational governance, had a positive incentivizing effect on the project performance. The psychology and behavior of the construction agent played a partial mediating role. The results provide a policy implication for city government to improve the incentive system for agent construction of security housing projects.